ChemInform Abstract: Bromopyrrole Alkaloids from a Marine Sponge Agelas sp. Issue 44 (4th November 2014) - Kusama, Taishi; Tanaka, Naonobu; Takahashi‐Nakaguchi, Azusa; Gonoi, Tohru; Fromont, Jane; Kobayashi, Jun'ichi
Abstract Five new bromopyrrole alkaloids, 2‐bromokeramadine, 2‐bromo‐9, 10‐dihydrokeramadine (II), tauroacidins C and D, and mukanadin G (II) are isolated together with three known bromopyrrole alkaloids.